Kandungan alkaloid dan flavonoid tiga spesies anggrek berpotensi obat dari Kawasan Gunung Gumitir Kabupaten Jember - Setyati, Dwi; Lutfianasari, Desy; Ratnasari, Tri (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i01.p02, 2022)
Orchid plants are known as ornamental plants, and also as a potential medicine including Dendrobium linearifolium Teijs & Binn., Bulbophyllum odoratum (Blume) Lindl., and Vanda tricolor Lindl. Medicinal properties in plants are due to the presence of secondary metabolites, including alkaloids and flavonoids. This study aims to determine the alkaloid and flavonoid content of three species that are considered as potential medicine from the Gumitir Mountain area, Jember Regency. Three types of orchids was separated between the stems, pseudobulbs and leaves were then dried and mashed until they got a powder. Extraction of orchid powder and quantitatively measured by spectrophotometry. The average alkaloid and flavonoid content in the leaves. The alkaloid content of three species is Dendrobium linearifolium Teijsm. & Binn. (43.84 mgBE/g), pseudobulb and leaves Bulbophyllum odoratum (Blume) Lindl. (21.91 mgBE/g) and (18.01 mgBE/g, the lowest was Vanda tricolor Lindl (9.35 mgBE/g). The highest flavonoid content was found in the leaves of Dendrobium linearifolium Teijsm. & Binn. (219.59 mgQE/g) followed by leaves Bulbophyllum odoratum (Blume) Lindl. (132.21 mgQE/g) and Vanda tricolo r Lindl leaves (122.69 mgQE/g) and the lowest was stem Dendrobium linearifolium Teijs & Binn (56.26 mgQE/g).